Flexible and Wearable Volatile Organic Compounds (VOCs) Sensing: Development and Future Perspectives - Ren, Houcheng (European Journal of Applied Sciences, 2024)
Wearable gas sensors based on flexible design can be coupled to the vicinity of biological or environmental interfaces for detecting of volatile organic compounds (VOCs), with greatly simplified sample collection, storage, and analysis process. The flexible devices expand the detection form of sensors and provide continuous and real-time insights for gas detections. Based on wearable exhalation detection system, such as smart facemasks, in-situ and dynamic detection of various VOCs during diet and exercise regulation has been achieved. Thus, the wearable detection provides a unique perspective for biological metabolic activities and important technical support for personalized health detection and disease diagnosis such as pathogens from aerosol. This article introduces the development and application of the flexible wearable in-situ gas sensing technology and provides a detail outlook of the future perspectives in this field.